Efeitos do uso de cocaína no envelhecimento celular : a relação entre o transtorno por uso de cocaína e telômeros - Niederauer, João Paulo Ottolia (2021)
The main objective of this work was to investigate the effects of the Cocaine use disorder in the cellular aging, specifically in the length of the telomeres of women cocaine users in treatment for detoxification. First, a theoretical foundation was made about the proposed theme. Cocaine use disorder and the function of telomeres were described and, finally, the relationship between cocaine use and telomeres length was described. Afterwards, an empirical article was developed with the objective of investigating the impact of more severe use of cocaine on the length of the telomeres and whether the shortening of telomeres would be associated with more severe withdrawal symptoms at the end of the detox. For the empirical article, 100 female cocaine users and 150 female controls were recruited. Cocaine users came from an inpatient unit for detoxification and controls for convenience. The Addiction Severity Index (ASI-6) was applied to collect information regarding the pattern of drug use, sociodemographic and clinical data. The Cocaine Selective Severity Assessment (CSSA) was applied to collect withdrawal symptoms at the end of hospitalization. SCID-IV was applied to assess psychiatric diagnosis. Finally, the Childhood Trauma Questionnaire (CTQ) was applied to data on childhood trauma. The qPCR method was used to quantify the telomeres. The theorical foundation found a relationship between substance use disorder and telomere length. In the empirical article, comparison of the average telomere length revealed that female cocaine users had lower telomeres than healthy controls. Women with cocaine use who had more severe use had shorter telomeres than the group with less severe use. ANOVA revealed group effect and age between COC and CS, and group effect between COC+sev and COC-sev, controlling for age, years of study, body mass index and childhood maltreatment. Finally, female users with shorter telomeres showed more severe withdrawal symptoms at the end of hospitalization, especially regarding cleft and sleep. This dissertation advances the understanding of the effects of the disorder caused by cocaine on cell aging. This study suggests that severity of cocaine use is associated with decreased telomere length. In addition, shortened telomeres are associated with worse withdrawal symptoms at the end of hospitalization. The results of the empirical article and the discussion of the theory advance in the identification of telomeres as a target for the evaluation and treatment of cocaine users in the process of detoxification. The present study provides new results that can identify more effective interventions for drug treatment.